Employing the Short Story with Pictures to Enhance the Language Development of Deaf and Hard of Hearing Students from the Point of view of their teachers - Al-Zahrani, Hessa Saleh Waqit; Abdelaziz, Omar Fawwaz (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to determine the level of employing the short story with pictures in enhancing the linguistic development of deaf and hard-of-hearing students from the point of view of their teachers in the cities of Makkah and Jeddah. The current study used the descriptive survey method, and the study population consisted of all male and female teachers of deaf and hard-of-hearing students in government institutes and programs. The sample of the study was (110) male and female teachers, of them (43) male teachers and (67) female teachers are teachers of deaf and hard-of-hearing students working in government institutes and programs in the cities of Makkah Al-Mukaramah and Jeddah.To achieve the objectives of the study, the researchers developed a questionnaire to determine the level of employing the short story with pictures in promoting the linguistic development of deaf and hard-of-hearing students from the point of view of their teachers. The validity and reliability of the questionnaire was verified. The results of the study indicate that the level of employing the short story with pictures in enhancing the linguistic development of deaf and hard-of-hearing students from the point of view of their teachers came at a high level, it reached 4.26. and that the fourth axis in the study tool is "effectiveness and impact The Short Story with Pictures " came first with an arithmetic average of 4.35, at a high level. The study recommends activating the training programs on employing the Short Story with Pictures in promoting linguistic development during service for teachers with hearing disabilities and motivating them to participate in courses and workshops related to the use of short stories in promoting linguistic development while exchanging experiences with their colleagues. and provide appropriate financial support to provide the materials needed by teachers with disabilities.
Keywords: deaf and hard of hearing; short story with pictures; linguistic development